Six Drivers to Face the XXI Century Challenges and Build the New Healthcare System: “La Salute in Movimento” Manifesto - Blasi, Francesco; Caiani, Enrico Gianluca; Cereda, Matteo Giuseppe; Donetti, Daniela; Montorsi, Marco; Panella, Vincenzo; Panina, Gaia; Pelagalli, Felicia; Speroni, Elisabetta (Frontiers in Public Health, 2022)
The aging of the population, the burden of chronic diseases, possible new pandemics are the challenges for healthcare in the XXI century. Technological innovations and the national recovery and resilience plan within the European Union are opportunities to implement changes and renovate the current healthcare system in Italy, to guarantee equal access to health services. Considering such scenario, a panel of Italian experts gathered in a multidisciplinary Think Tank to discuss possible design of concepts at the basis of a new healthcare system. These ideas were summarized in a manifesto with six drivers for change: vision, governance, competence, intelligence, humanity and relationship. Each driver was linked to an action to actively move towards a new healthcare system based on trust between science, citizens and institutions.